The economics of accounting standard setting - Bromwich, Michael (Prentice-Hall, 1985)
Quality of corporate financial reporting potentially rises if standard accounting rules/principles are of high quality and compliance to them is strongly enforced. But the book reveals immediate problem of political intervention facing market economies, their investors and creditors. This study should help standard setters, securities regulators, serious researchers on accounting and students at large to understand how interveners make such interpretations.